Hazardous alcohol use and alcohol-related harm in rural and remote communities: a scoping review - Friesen, Erik Loewen; Bailey, Jacob; Hyett, Sarah; Sedighi, Sina; de Snoo, Mitchell Lennox; Williams, Kenneth; Barry, Rebecca; Erickson, Anders; Foroutan, Farid; Selby, Peter; Rosella, Laura; Kurdyak, Paul (The Lancet. Public health, 2022)
Alcohol use is a major risk factor for death and disease worldwide and alcohol-related harms appear to be more prevalent in rural and remote, relative to urban, communities. This Review synthesised international research on rural–urban disparities in hazardous and harmful alcohol use and risk factors for these outcomes within rural and remote communities. 280 studies from 49 countries were included in the Scoping Review. Most studies (60%) found rural, relative to urban, residence to be associated with an increased likelihood of hazardous alcohol use or alcohol-related harm. This proportion increased between 1990 and 2019 and varied by country, age group, and outcome type, being highest in Australia, among young adults, and for more severe alcohol-related harms, such as drink driving and alcohol-related suicide. Improved public health strategies to reduce the burden of alcohol use in rural communities are required but their efficacy will depend on how well they are tailored to the unique needs of the region they are implemented in.